Exploration of the resistance mechanism of Botrytis cinerea to pyrimethanil - Liting Wu; Hongjiao Mu; Rui Xiao; Zhiqiu Qi; Rujun Zhou (Journal of Plant Diseases and Protection, 2025)

Phosphorus speciation, controlling factors, and ecological risk assessment in lagoon sediments: a case study of the Shamei Lagoon, Qionghai, Hainan - Kun Yuan; Xuan Mu; Guangning Xiao; Kexin Li; Wantong Zhou; Rui Wang; Shisheng Wang (Frontiers in Marine Science, 2025)
The Shamei Lagoon in Qionghai, Hainan, is an ecologically significant coastal wetland system that has recently faced increasing ecological risks due to phosphorus (P) pollution. In this study, 22 sediment samples were systematically collected from the main lagoon body, river inlets, and the transitional zone to the open sea. A comprehensive approach incorporating standardized phosphorus fractionation, spatial interpolation, redundancy analysis, and ecological risk assessment was used to investigate P speciation, spatial distribution patterns, controlling factors, and ecological risks. The results showed that: (1) Total phosphorus (TP) concentrations ranged from 261.87 to 875.74 mg/kg, with a mean of 415.72 mg/kg, comparable to typical lagoons in China. Inorganic phosphorus (IP) dominated the P fractions (mean: 317.70 mg/kg), with Fe/Al-bound phosphorus (Fe/Al-P, mean: 183.52 mg/kg) markedly exceeding Ca-bound phosphorus (Ca-P, mean: 105.88 mg/kg). Organic phosphorus (OP) had the lowest contribution (mean: 98.02 mg/kg). (2) The primary sources of P pollution were agricultural runoff and aquaculture waste, industrial discharges and vessel leakage, and regional calcareous deposition. High TP and OP concentrations were concentrated in the southwest river inlet zone, directly linked to fertilizer runoff and tourism-related wastewater. IP levels were elevated in the southern region, driven by hydrodynamic processes. Fe/Al-P was enriched in the central lagoon, likely associated with oil degradation from vessels. Secondary peaks of Ca-P occurred in the southwest aquaculture zone and the northeastern mangrove area, attributed to feed residues and shell debris, respectively. (3) Cation exchange capacity (CEC) was identified as the primary controlling factor for spatial variation in P speciation (explained variance: 46.0%, p < 0.01), followed by organic matter (OM), while pH exhibited a marked negative regulatory effect. (4) At 45.5% of sampling sites, TP levels exceeded the ecological safety threshold (600 mg/kg), and 18 sites, mainly located near the river mouth and central lagoon, were classified as heavily polluted, posing a threat to aquatic ecological security. These findings indicate that sediment P pollution in the Shamei Lagoon is driven by multiple anthropogenic activities. Mitigation strategies should prioritize control of agricultural non-point sources, aquaculture residues, and vessel oil pollution, along with sediment remediation focused on enhancing CEC.

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)